Chinese Medicine Constitution that Influences Sleep Quality and Fatigue among Chinese Nurses Working in Shifts in Japan and China - Wang, Zhixia; Hohashi, Naohiro; Wu, Xiaoyu (Journal of Rural Community Nursing Practice, 2023)
Nurses who work in shifts may face poor sleep quality and oppressive fatigue. The purpose of this study was to clarify Chinese medicine constitution that influences sleep quality and fatigue among Chinese nurses engaged in shift work. Considering that these conditions might differ according to living environments, studies were conducted both in Japan and China. Data were gathered using the attributes of nurses, the Pittsburgh Sleep Quality Index to evaluate sleep quality, the Jikaku-sho shirabe to evaluate fatigue, and the Constitution in Chinese Medicine Questionnaire, which evaluates Chinese medicine constitution according to nine criteria. The survey was conducted via internet, with data analyzed from 100 Chinese subjects in Japan and 100 Chinese subjects in China. Increase in age, living in China, Qi-deficiency constitution and Blood-stasis constitution were causal factors for lower sleep quality. Sleep quality was significantly lower among nurses in China than those in Japan. The following factors were observed to be causal factors for increased fatigue: longer histories of working in shifts, living in Japan, poorer quality sleep, Qi-deficiency constitution, Yang- and Yin-deficiency constitution, Qi-stagnation constitution and Inherited special constitution. Nurses in Japan showed significantly greater fatigue at the end of a night shift than did those in China. It is suggested that adjustments of Qi-deficiency constitution and Blood-stasis constitution can improve sleep quality in nurses who work in shifts. We believe that improving sleep quality and making adjustments to the five types of Chinese medicine constitution can work to reduce fatigue.